Supervisi Pendidikan: Bukan Sekadar Pengawas, Melainkan Jembatan Transformasi Kualitas Guru dan Sekolah - Sangadah, Siti; Fani, Farid Al; Fatimah, Meti (Lembaga Yasin AlSys, 2026)
Educational supervision is a strategic element in the development of educational resources, particularly in improving teacher quality and the standard of teaching and learning in schools. This article aims to explain the nature of supervision, analyze its implementation, and describe its contribution to the development of teacher competence and school management. Using a literature review method, this study examines various journals, books, and research reports relevant to academic and managerial supervision. The review findings show that supervision functions as a systematic professional development process that emphasizes ongoing support through observation, reflection, and continuous guidance. Supervision also serves to maintain the quality standards of learning and to strengthen school governance by identifying institutional constraints and promoting continuous improvement. In addition, supervision has a significant impact on enhancing teacher performance, teaching motivation, and the effectiveness of the learning process. These findings affirm that supervision functions not merely as a control mechanism, but also as a comprehensive and sustainable strategy for developing educational resources, thereby becoming an essential instrument for realizing higher-quality education.